Left atrial scar burden in sinus rhythm differs from atrial fibrillation using automated voltage analysis during radiofrequency ablation for atrial fibrillation. (24th May 2021) - Mannion, J; Lennon, SJ; Kenny, A; Boles, U
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Scar burden in atrial fibrillation (AF) can be overestimated due to many factors. Scar burden has prognostic value and substrates considered for ablation by some electrophysiologists. We compared left atrial (LA) scar voltage in AF to sinus rhythm (SR) using voltage histogram analysis (VHA) of those undergoing pulmonary vein isolation (PVI) for persistent AF (PeAF). We believe this is the first study analysing LA scar location in SR and AF using VHA. Methods: We retrospectively analysed 120 anatomical segments (AS) and whole LA voltages (N= 10 patients, mean age 68 ± 7, 4 females) in SR and AF. Fast anatomical maps (FAM) were grouped into 6 AS in AF and SR: Anterior, Posterior, Roof, Floor, Septal and Lateral AS, which were analysed via VHA (Figure 1) in 10 voltage ranges between 0mV-0.5mV. Total LA area in each voltage aliquot was recorded in SR and AF, taking diseased LA as 0.2-0.5mV and dense LA scar as <0.2mV. The pulmonary veins, mitral annulus and trans-septal puncture sites were excluded from analyses. We included patients over age 18 with PeAF who had de novo PVI with no extra ablation lines, maps with >1000 voltage points in both rhythms and uniform procedure involving initial mapping in AF then remapping in SR after PVI. Statistical analyses conducted with IBM SPSS v.26. Results: Total LA scar burden was greater in AF (Mean 142.76 mm², SD ± 138.78mm²) than SR (Mean 109mm², SD ± 107.8mm²), p= <0.0001, Table 1. Scar correlation in SR and AF had a good relationship, R = 0.416 (p= <0.001). Every 1mm² of scar identified during SR yielded a mean of 1.54mm² in AF, (p= <0.001). Conclusions: AF was associated with higher scar burden in the Roof, Anterior, Lateral and Posterior AS. Dense LA scar (≤ 0.2mV) on the Posterior AS was significantly higher in AF, while in other AS was comparable to SR. Mapping substrate in AF, especially the posterior wall, may be misleading as scar burden may be overestimated when compared to SR.